2015
DOI: 10.1159/000440666
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Preoperative Biopsy Is a Risk Factor for Positive Surgical Margins in Organ-Confined Prostate Cancer Treated with Nerve-Sparing Robot-Assisted Radical Prostatectomy

Abstract: Purpose: Positive surgical margins (PSM) during robot-assisted radical prostatectomy (RARP) negatively influence patients' prognosis. The aim of our study was to identify risk factors for PSM in patients with organ-confined prostate cancer (PCa). Methods: A clinical database of all patients that underwent a RARP at our institution was used. Uni- and multivariable logistic regression analyses were conducted on the PSM rates for all patients with organ-confined PCa. Results: Altogether, 1,600 patients were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Indeed, in recent years, mpMRI of the prostate has shown to be an effective tool for identifying areas of suspicion that correlate with cancer upgrading and upstaging [22,23,24]. Moreover, it has recently been shown that mpMRI is an effective tool for both local staging and planning nerve-sparing surgery in patients undergoing RP [25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in recent years, mpMRI of the prostate has shown to be an effective tool for identifying areas of suspicion that correlate with cancer upgrading and upstaging [22,23,24]. Moreover, it has recently been shown that mpMRI is an effective tool for both local staging and planning nerve-sparing surgery in patients undergoing RP [25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…Available population data demonstrate short-term advantages of RARP relative to ORP, such as fewer blood transfusions, fewer complications and shorter length of hospital stay [4] . Additionally, RARP is at least equivalent [5] if not superior [6] to ORP in terms of margin rates [7] . Moreover, the advantage of pelvic lymph node dissection (PLND) extent and/or yield at RARP vs. ORP is also being debated [8,9] .…”
Section: Introductionmentioning
confidence: 98%
“…And then, we eliminated 153 studies based on screening the titles and abstract. After full‐text assessing of 45 studies were performed, eventually 22 studies (Allaparthi, Hoang, Dhanani, & Tuerk, ; Butow et al, ; Caliskan, Kaba, Koca, & Ozturk, ; Chang, Moon, Gianduzzo, & Eden, ; Chu et al, ; Descazeaud, Zerbib, Vieillefond, Debre, & Peyromaure, ; Foley, Bott, Thomas, Parkinson, & Kirby, ; Freedland et al, ; Galfano et al, ; Goetzl, Krebill, Griebling, & Thrasher, ; Hong et al, ; Kim et al, ; Labanaris et al, ; Lallas et al, ; Levinson et al, ; Marchetti, Shikanov, Razmaria, Zagaja, & Shalhav, ; Msezane et al, ; Olsson et al, ; Pettus et al, ; Yadav et al, ; Yasui et al, ; Zorn et al, ) were enrolled in our meta‐analysis. The characteristics of them were introduced in Table .…”
Section: Resultsmentioning
confidence: 99%